2016
DOI: 10.1016/j.chom.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

NLRX1 Sequesters STING to Negatively Regulate the Interferon Response, Thereby Facilitating the Replication of HIV-1 and DNA Viruses

Abstract: SUMMARY Understanding the negative regulators of anti-viral immune responses will be critical for advancing immune-modulated antiviral strategies. NLRX1, an NLR protein that negatively regulates innate immunity, was previously identified in an unbiased siRNA screen as required for HIV infection. We find that NLRX1 depletion results in impaired nuclear import of HIV-1 DNA in human monocytic cells. Additionally, NLRX1 was observed to reduce type-I interferon (IFN-I) and cytokines in response to HIV-1 reverse-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
135
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(138 citation statements)
references
References 47 publications
3
135
0
Order By: Relevance
“…Furthermore, NLRX1 has been demonstrated to inhibit STING signalling by blocking the interaction between STING and TANK-binding kinase 1 (TBK1), which is required for the induction of IFN-1 in response to DNA. Moreover, NLRX1 -/-cells express a higher level of type 1 interferon during HIV-1 infection or treatment with cyclic GAMP or cyclic di-GMP, which triggers STING-dependent responses [109]. However, NLRX1 regulation is quite complex and seems to occur via cell typeand signal-dependent mechanisms; the above findings suggest the role of NLRX1 in the regulation of IFN during viral infection as well as the regulation and activation of inflammasomes.…”
Section: Nlrx1mentioning
confidence: 96%
“…Furthermore, NLRX1 has been demonstrated to inhibit STING signalling by blocking the interaction between STING and TANK-binding kinase 1 (TBK1), which is required for the induction of IFN-1 in response to DNA. Moreover, NLRX1 -/-cells express a higher level of type 1 interferon during HIV-1 infection or treatment with cyclic GAMP or cyclic di-GMP, which triggers STING-dependent responses [109]. However, NLRX1 regulation is quite complex and seems to occur via cell typeand signal-dependent mechanisms; the above findings suggest the role of NLRX1 in the regulation of IFN during viral infection as well as the regulation and activation of inflammasomes.…”
Section: Nlrx1mentioning
confidence: 96%
“…NLRC3 interacts with both STING and TBK1 and disturbs STING translocation and STING-TBK1 association to block type I IFN production (49). Interestingly, NLRX1 also inhibits the STING-mediated signaling pathway by impeding the STING-TBK1 interaction (29). The mechanism discovered in the present study, where NLRX1 attenuates virus-induced IFN signaling by targeting MAVS for degradation, presents a new perspective for understanding the action of the host innate immune system.…”
Section: Discussionmentioning
confidence: 62%
“…Although evidence from a recent report indicated that NLRX1 may act as a proviral host factor in infection by human immunodeficiency virus type 1 and some DNA viruses (29), the role of NLRX1 in HCV infection remains obscure. To investigate whether NLRX1 modulates HCV propagation, we constructed a stable NLRX1-silenced cell line using HLCZ01 cells, which support the entire life cycle of HCV (see details in our previous study [33]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations